Local Wisdom and Gender Equality in Joint Property Division: An Islamic Legal Perspective from Malaysia - Mat Hussin, Mohd Norhusairi; Arifah, Risma Nur; Aisyah, Siti; Daud, Mohd Zaidi; Samah, Mahamatayuding (De Jure: Jurnal Hukum dan Syari'ah, 2025)
This study investigates the practice of harta sepencarian (joint matrimonial property) within the Malay community in Malaysia, focusing on the interaction between Islamic law, local customs, particularly Adat Perpatih and Adat Temenggung, and cultural values. Using a normative legal approach supported by content analysis, the research examines whether current legal frameworks and social practices align with the principles of justice, gender equity, and the objectives of Islamic law (maqāṣid al-shari’ah), especially the protection of wealth (ḥifẓ al-māl), well-being (ḥifẓ al-nafs), and dignity and lineage (ḥifẓ al-ʿirḍ wa al-nasab). The findings reveal that harta sepencarian represents a hybrid legal model, integrating statutory Islamic family law with indigenous Malay traditions. The increasing acknowledgement of women’s domestic and economic roles significantly influences decisions regarding asset division. While there appears to be a general harmony between religious and customary principles, the study highlights key challenges, such as the lack of legal clarity regarding indirect contributions and inconsistencies in dispute resolution processes. To bridge these gaps, the research advocates for the formalisation of equitable legal standards that incorporate both Islamic jurisprudence and customary wisdom. By doing so, harta sepencarian can evolve into a more just and culturally resonant framework for managing marital property within the Malay Muslim community.